Becoming-Performance: Body, Time, and Deterritorialization in the Adaptation of The Swan Song - Ilham Rifandi; Saaduddin Saaduddin (Melayu Arts and Performance Journal, 2025)
This article analyzes Terbuang dalam Waktu, a performance by Teater Balai, presented at Alek Teater IX at UPTD Taman Budaya Sumatera Barat in September 2025. Employing a performative dramaturgical approach grounded in the conceptual framework of Gilles Deleuze, the article examines how body and time are staged as fields of non-linear intensity rather than as conventional dramatic representations. Adapted from The Swan Song (1887) by Anton Chekhov, the performance presents two versions of Vasili Svietlovidoff—young and old—appearing simultaneously on stage, producing a temporal fold that collapses past and present within a single performative space. The analysis identifies three key strategies: dramatic non-linearity through temporal folding, the deterritorialization of the Minangkabau body within a Western classical text, and an assemblage of space–body–light that generates an affective experience without a singular center of meaning. These findings affirm the work as a post-realist dramaturgical experiment positioning the actor’s body as a temporal archive and a site of cultural identity negotiation in contemporary Indonesian theatre.